Managing Deep Learning to Encourage Independence in Elementary School Students: A Qualitative Case Study - Purwanti Purwanti; Enung Hasanah; Muhammad Zuhaery (LP. Ma'arif Janggan Magetan, 2025)
Instilling learning independence from an early age is an important step towards creating students who are independent, confident, and capable of lifelong learning. This independence plays an important role in supporting academic success as well as shaping students' character and skills in facing future challenges. This research aims to analyze deep learning management in shaping the learning independence of elementary school students. The approach used is descriptive qualitative with a case study at SD Muhammadiyah Danunegaran. Data were collected through interviews, observations, and documentation. Informants were selected by purposive sampling consisting of class teachers and students. Data analysis used thematic techniques assisted by ATLAS.ti. The results showed seven main themes in deep learning management, including planning, implementation, evaluation, characteristics and importance of learning independence, supporting factors, and challenges. Planning is done collaboratively, implementation places teachers as facilitators, and evaluation uses rubrics, checklists, and observations. Independence is characterized by confidence, initiative, responsibility, and self-learning. School culture is supportive, while challenges come from students' diverse characters and parenting patterns. The findings contribute to the management of deep learning practices in elementary schools, emphasizing how well-managed learning processes can foster students’ independence, as well as their critical and reflective thinking in constructing knowledge.